(untitled) (Pharmacy Practice, 2016)
Background: As oral contraceptive pills are available over the counter in pharmacies, pharmacists are professionally responsible for checking and informing patients about every aspect of taking these drugs. Simulated patient method is a new and robust way to evaluate professional performance of pharmacists. Objective: The aim of the present study was to evaluate the pharmacy practice of Iranian pharmacists regarding over-the-counter use of oral contraceptive pills using simulated patient method. Methods: Simulated patients visited pharmacy with a prescription containing ciprofloxacin and asked for oral contraceptive pills. The pharmacist was expected to ask important questions for using these drugs and to inform the patient about them properly. Moreover, the Pharmacists should advise patients in regard to the possible interaction. Results: Ninety four pharmacists participated in this study. In 24 (25.3%) visits, the liable pharmacist was not present at the time of purchase. Furthermore, In 13 (18.57 %) visits by the simulated patients, the liable pharmacists did not pay any attention to the simulated patients even when they asked for consultation. Twenty nine (41.43%) pharmacists did not ask any question during dispensing. Nausea was the most frequent described side effect by pharmacists (27 (38.57%)). Yet important adverse effects of oral contraceptive pills were not mentioned by the pharmacists except for few ones. Only twelve (17.14%) pharmacists mentioned the possible interaction. There was a significant relation between the pharmacists’ gender and detection of possible interaction (p value= 0.048). Conclusion: The quality of the pharmacists’ consultations regarding the over the counter use of oral contraceptive pills was not satisfactory and required improvement.